Enhancing analgesia in acute renal colic pain: a randomized controlled trial of gabapentin adjunct to ketorolac-based regimen - Kianpour, Parisa; Valavioun, Parmis; Payandemehr, Pooya; Safaei, Arash; Borhani, Yasaman; Honarmand, Hooshyar; Mojtahedzadeh, Mojtaba; Basiri, Kamal; karimpour-Razkenari, Elahe; Najmeddin, Farhad (Frontiers in Pain Research, 2024)
BackgroundRenal colic is characterized by severe pain that is highly disabling. Gabapentin, an antiepileptic medication, is often recommended as a first-line therapy for neuropathic pain. However, its effectiveness in managing somatic pain, which is defined as the result of activity by pain receptors in the deep tissues, such as renal colic pain, is not as well-established.MethodA phase 3 randomized clinical trial was conducted to evaluate the adjuvant analgesic effects of gabapentin on acute renal colic pain. Eligible patients participated in the study via random allocation to the control or gabapentin groups using the block randomization method. All patients received a shared regimen of ketorolac and rescue morphine as the conventional analgesic treatment for renal colic pain. Gabapentin was added as an adjuvant analgesic for the gabapentin group.ResultA total of 63 individuals with an average age of 41.35 ± 13.08, were enrolled and completed the study. At the time of admission, there were no significant differences between the baseline characteristics of two groups, with exception of weight. The gabapentin group showed a significantly higher percentage of patients with pain severity of less than 5 after 60 and 90 min, as well as a significantly lower percentage of morphine rescue requirement and total morphine intake (mg) and mg/kg.ConclusionIn cases of acute renal colic, gabapentin significantly decreases both the amount of morphine required and the degree of pain, indicating that it may be a useful adjutant to standard analgesic regimens. Treatment regimens that include gabapentin may help individuals manage their pain and become less reliant on opioids. Clinical Trial Registrationhttps://irct.behdasht.gov.ir/trial/56066, identifier: IRCT20200322046833N2.